Filtered Predictive PI Controller for WirelessHART Networked Systems - Hassan, S.M. (Springer, 2020)
Recently, increasing attention has been paid towards applying wireless technology for control. This is due to its advantages of flexibility, scalability, use of fewer cables and overall reduced operational cost compared to its wired counterpart. However, the technology is often affected by stochastic delay and high frequency noise. PIDs are ill-equipped to deal with these problems while model based controllers such as dead-time compensators (DTCs) like Smith predictor and internal model controllers (IMCs) are complex and require exact plant model for implementation. Â© 2020, Springer Nature Switzerland AG.